2005
DOI: 10.1007/s11258-005-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of sedimentation and nitrogen enrichment on wetland plant community development

Abstract: Many factors influence which plant species are found in a particular wetland. The species pool is composed of the species present in the seed bank and species able to disperse into the wetland, and many abiotic and biotic factors interact to influence a species performance and abundance in the plant community. Anthropogenic activities produce specific stressors on wetland systems that alter these abiotic and biotic interactions, potentially altering species composition. We simulated three common wetland hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Such spatial configuration of benched and graveled pads may facilitate the invasion and spread of ruderal plants into the intersected wetlands. In addition, the installation of these terrestrial barriers in water may induce sediment deposition and nutrient enrichment which change plant community development and create appropriate microhabitats for the establishment of non-native plants in wetlands (Miller and Zedler, 2003;Mahaney et al, 2004;Dube´et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such spatial configuration of benched and graveled pads may facilitate the invasion and spread of ruderal plants into the intersected wetlands. In addition, the installation of these terrestrial barriers in water may induce sediment deposition and nutrient enrichment which change plant community development and create appropriate microhabitats for the establishment of non-native plants in wetlands (Miller and Zedler, 2003;Mahaney et al, 2004;Dube´et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Freeland et al (1999) found that there were higher rates of deposition in wetlands adjacent to cultivated fields in North Dakota. Sediments and nutrients deposited in wetlands impact the vegetation and hydrology of the systems (Mahaney et al 2005;Preston et al 2013).…”
Section: Soil Change In Wetlandsmentioning
confidence: 99%
“…), via changing hydrologic patterns, sedimentation, and nutrient enrichment (Wardrop and Brooks , Mahaney et al. , ).…”
Section: Introductionmentioning
confidence: 99%